Sustainable Stabilization of Expansive Soil Using Fly Ash, Olive Cake Ash, and Zeolite: An Experimental and Numerical Study - Abu Yosef, Suleiman; Balkaya, Muge; Abu Arra, Ahmad (SPRINGER HEIDELBERG, 2026)
Expansive soils are prone to volume instability due to moisture variations, leading to significant damage to structures and pavements. To meet construction stability requirements, improving the performance and strength of these soils is crucial. This study investigates the stabilization of expansive soils using fly ash (FA), olive cake ash (OCA), and zeolite, both individually and in mixtures, to enhance soil strength, improve compaction, and reduce settlement, free swell, and swell pressure. The research involved detailed experimentation and finite element simulations of a road construction. The results demonstrated that the unconfined compressive strength of uncured samples with 20% FA, and 10% FA + 5% zeolite additives significantly increased to 405 kPa and 409 kPa, respectively, from a baseline of 236 kPa. OCA yielded improved strength after 28 days (529 kPa) due to pozzolanic activity. Most notably, the 10% FA + 5% zeolite mix reduced soil swelling from 18.59 to 1.77%, leading to a 90.48% decrease in free swell percentage. Additionally, FA and OCA improved consolidation characteristics and reduced compressibility. These results advance soil stabilization techniques for expansive soils, promoting more sustainable construction practices.
Keywords: Expansive soil; Fly ash; Olive cake ash; Zeolite; Sustainability; Finite element method; ENGINEERING PROPERTIES; CLAY; Science & Technology - Other Topics